Relationships between safety climate perception, job satisfaction and occupational safety health management system with occupational accident at small medium industries at two localities in Selangor, Malaysia - Mohamed, Noradila (2014)
Small medium industries in Malaysia have grown rapidly and face challenges such as a high rate of occupational accidents in workplaces. The frequency of occupational accident in small medium industries decreased from 2008 in general, but fluctuated each year, which shows that improvement is needed in handling safety and health of the employees. It is believed that safety climate perception, job satisfaction and occupational safety health management system influence occupational accident in an organization. Therefore, to facilitate the expansion of current theoretical perspectives in this research area, this research attempts to study the relationship between safety climate perception, job satisfaction and occupational safety health management system practices with occupational accident. A cross-sectional design was employed for data collection. A safety audit checklist and a self-administered questionnaire were distributed to the involved small medium industries from March 2013 until August 2013 for data collection. The results were based on seven small medium manufacturing industries in Shah Alam and Kuala Langat, Selangor. The response rate was 86 percent (n=237). The findings show that safety climate perception and job satisfaction of employees were high in small medium industries. Most of the organizations involved showed low compliance with the occupational safety health management system. The findings also revealed that 36% of the respondent were involved in occupational accident in the last six months. In addition, Kuala Langat showed significantly higher scores of safety climate perception, job satisfaction, occupational safety health management system and occupational accident than Shah Alam. High compliance with the occupational safety health management also showed a higher score for safety climate perception and job satisfaction, and lower frequency of occupational accident. Findings also showed that there were significant relationships between safety climate perception, job satisfaction and occupational safety health management system with occupational accident in the organizations (p<0.05). The findings also revealed safety climate perception, occupational safety health management system, age and middle income are predictors for occupational accident.